NR-Connect: Development of UNIMAS Non-Resident Mobile Application - Muhammad Hafiz, Abu Bakar; Abdul Rahman, Mat; Hamizan, Sharbini (UNIMAS Publisher, 2025)
The NR-Connect application was developed to address the communication and emergency response needs in between NR students, felos, and administrator of Universiti Malaysia Sarawak (UNIMAS). This project leveraged the Waterfall methodology to systematically design, implement, and verify an integrated platform combining features for news dissemination, event management, and emergency reporting. The application utilizes Flutter for the front-end and Firebase for back-end services, ensuring a seamless user experience across various devices. Key functionalities include a login and registration system, a horizontal scrollable menu for event categories, and real-time data fetching from Firestore. The evaluation of NR-Connect highlighted significant improvements in information accessibility and response efficiency for the university community. Feedback from users indicated high satisfaction with the application's usability and relevance. Future enhancements will focus on expanding features, improving performance, and integrating advanced analytics to further support the dynamic needs of UNIMAS students, felos, and administrator.